In vitro antifilarial potential of the flower and stem extracts of Leucas cephalotes on cattle filarial parasite Setaria cervi - Ahmed, Qamar Uddin; Parveen, Nazneen; Khan, N. U.; Singhal, K. C. (Natural Remedies, Bangalore, India., 2002)
Objective: To assess the potential antifilarial activity of the aqueous and alcoholic extracts of flower and stem prepared from L. cephalotes. Materials and methods: The effect of extracts was studied on the spontaneous movements of wholeworm and the nerve-muscle preparation of Setaria cervi and on the survival of microfilariae in vitro. Results: Alcoholic extracts of the flower and stem caused inhibition of the spontaneous movements of the wholeworm and of the nerve-muscle preparation of S. cervi. However, aqueous extracts of the flower and stem failed to modify the movements of the whole worm while caused irreversible paralysis of nerve muscle preparation characterized by decrease in rate, tone and amplitude of contractions. This may be due to failure of penetration of cuticular barrier by the aqueous extract. The alcoholic extract also decreased the duration of survival of microfilariae of S.cervi. Conclusion: L. cephalotes exhibits potential antifilarial activity against both the adult worms and the microfilariae of Setaria cervi. Further work is required to find its utility in human filarial infections. Keyword: Leucas cephalotes, Setaria cervi antifilarial activity, microfilaricidal.